Faktor – Faktor yang Mempengaruhi Minat Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan (PBB) di Desa Banyumas Kecamatan Stabat Kabupaten Langkat - Arnida Wahyuni Lubis; Sandra Hidayani (VISA: Journal of Vision and Ideas, 2023)
This research activity was carried out with the aim of knowing the factors that could influence people's interest in paying land and building taxes in Banyumas Village and what efforts were taken by the Banyumas Village government in increasing taxpayer compliance in paying land and building taxes. The research conducted by the researcher is a qualitative research type. The data used by researchers are qualitative data types. The results of the study can be concluded that the factors that influence people's interest in paying Land and Building Tax (PBB) in Banyumas Village are the community knowledge factor about the importance of paying taxes, the community understanding factor about Tax Regulations, the public awareness factor in paying Land and Building Tax (PBB), and tax services provided to the public. Keywords : Influence, Land and building tax,Interest